The binary of gender-based spaces in schools: A heterotopia study in Yogyakarta - Apriantika, Sasiana Gilar; Supraja, Muhamad; Itriyati, Fina (SIMULACRA: JURNAL SOSIOLOGI, 2024)
This study aims to explore how schools legitimize public as gender based power spaces. This research uses a qualitative approach, aspecially caes study methode. This research uses the theory of the heterotopia concept by Michel Foucault. Research findings indicate that there is gender-based spatial polarization, particularly in engaging in activities outside class hours. The hall, aisle, and canteen are predominantly occupied by male students, while the classrooms are mostly occupied by female students. Masculinity as a gender role taught to male students makes them more familiar with activities and relationships in public spaces. The traits of dominance and bravery make male students more comfortable socializing in their surroundings, allowing them to enjoy their breaktime in the hall and corridor. Meanwhile, femininity as a gender role taught to female students, makes them more at ease spending their break time in the classroom, because the classroom is the only space they posses personally. So, the responsibility of caring for and maintaining the classroom is also more heavily borne by female student. Schools legitimize space as a landscape that forms a binary relationship between private and public spaces. This polarization also emphasizes how schools serve as a platform to prevent individuals from becoming deviant and crisis actors.